2022
DOI: 10.1021/acsaem.1c04076
|View full text |Cite
|
Sign up to set email alerts
|

MnO2 Nanosheets on a Carbon Nanofiber Freestanding Film by Electrospinning and In Situ Spraying for Lithium and Sodium Storage

Abstract: Freestanding electrodes are critical for lithium-ion batteries (LIBs) and sodium-ion batteries (SIBs) with high energy density and long cycling stability. We fabricated freestanding MnO2 nanosheet-coated carbon nanofibers by synchronous in situ spraying of MnO2 nanosheets onto electrospinning polymer nanofibers, which might be a high-voltage electric field-induced assembly process. The designed film is used as anode material for LIBs and SIBs. It demonstrates good cycling stability without capacity loss after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…The battery-type capacitance accounted for 68% at a sweep rate of 5 mV s −1 , and the proportion of the diffusion-controlled capacitance gradually decreased as the sweep rate increased, to 25% at 50 mV s −1 . 47,48…”
Section: Resultsmentioning
confidence: 99%
“…The battery-type capacitance accounted for 68% at a sweep rate of 5 mV s −1 , and the proportion of the diffusion-controlled capacitance gradually decreased as the sweep rate increased, to 25% at 50 mV s −1 . 47,48…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, carbonaceous doping alloy‐based materials are good candidates for low‐temperature LIB anodes, as well as other materials with maximum theoretical capacities 45 such as CeVO 4, 48 Co 0.85 Se, 49 MnO 2, 45 CuSi 2 P 3, 50 Fe 2 O 3, 51 Mn 3 O 4, 52 Cu 2 WS 4, 53 Cu 2 O, 54 Li 3 VO 4, 55 Co 3 O 4, 56 NiO nanocrystals, nano‐Mn 2 O 3 particles, 57 MoS 2, 58,59 and MoSe 2 37 and SiO 2 . After carbonaceous doping, the low‐temperature characteristics could increase, which could be due to a stable SEI sheet 64‐71 . Nobili et al 59 used tin/graphite as the anode and applied it at −20°C (0.2 C, 1 mol/L LiPF 6 EC‐DEC‐DMC 1:1:1 as the electrolyte), the SEI resistance and Rct were lowered by 3 and 10 times, respectively, compared to the undoped material.…”
Section: Anode Cathode Separator and Electrolyte Of Low‐temperature Libsmentioning
confidence: 99%
“…After carbonaceous doping, the low-temperature characteristics could increase, which could be due to a stable SEI sheet. [64][65][66][67][68][69][70][71] Nobili et al 59 used tin/graphite as the anode and applied it at À20 C (0.2 C, 1 mol/L LiPF 6 EC-DEC-DMC 1:1:1 as the electrolyte), the SEI resistance and Rct were lowered by 3 and 10 times, respectively, compared to the undoped material. Li et al found that Fe-added Fe 3 C carbon nanofibers as an anode result in a better low-temperature performance of LIBs.…”
Section: Anodementioning
confidence: 99%
“…27,28 With the growing demand for wearable electronic devices for exible energy storage systems, a exible electrode with high energy density is of great importance for future application. Flexible electrodes are usually made from the methodologies of embedding the active materials in exible carbon nanobers, [29][30][31] growing them on exible conductive substrates, 32,33 and compositing them with two dimensional (2D) nanosheets, 34,35 which not only have good exibility, but can also provide higher energy density by avoiding the usage of an inactive binder and current collector compared to the traditional electrodes prepared via the slurry-coating method. [36][37][38] Graphene has proven to be a typical 2D carbon material with superior conductivity and large surface area.…”
Section: Introductionmentioning
confidence: 99%